(untitled) (Research, Society and Development, 2021)
Objectives: to visualize the impacts of social isolation in the practice of physical activities and its consequences for the elderly public, as well as to identify possible alternatives for the practice during isolation and forms of assistance to reduce the damages. Methodology: This is a systematic review of the SciELO, Medline, Lilacs and PUBMED databases. Only works published since 2010 were used to compose the sample space. After eliminating duplications, applying the inclusion and exclusion criteria and reading to discard works not related to the research theme, 15 articles remained. Results: The analysis of the selected works suggests that social isolation can cause damage, such as increasing the probability of the appearance of diseases, especially those related to the cardiac and psychological systems. Possible tools have been observed in the literature to combat the damage caused, such as the orientation of activities by conference, the encouragement of family and friends to practice physical and leisure activities and the development of public programs aimed at stimulating socialization. of the elderly public. Conclusion: social isolation increases the possibility of the appearance or worsening of symptoms related to depression or cardiomyopathies. In this sense, it is important that the government implements programs aimed at socializing, such as home visiting projects and encouraging physical activity at home, guiding family members to accompany the elderly in exercise and free time.